Ameriška geografija - Gosar, Anton (Geografski vestnik, 2024)
Geography in the United States of America has a long tradition of social associations, diverse activities, and research of natural and social phenomena. In the middle and second half of the 19th century, the following professional societies were founded: The American Geographic Society (AGS) and The National Geographic Society (NGS). At the dawn of the 20th century, the Association of American Geographers was formed, and was renamed 112 years later into the American Association of Geographers (AAG). In terms of commercial success, NGS stands out with its 135-year of tradition and of publishing the popular geographic magazine The National Geographic Magazine, as well its ownership of a commercial network and other financially successful companies. In terms of influencing the socio-political decision-making,the AGS has a better experience, as their members had a decisive influence on the formation of borders in Europe after the First World War. In 2024, AAG is celebrating 120 years of existence, and with it also the Annual Meetings of the AAG. The popularity of the gathering is demonstrated by more than 10,000 participants and by over 5,000 presentations. Since 2004, Slovenian geographers had 47 presentations at the AAG meetings.
Keywords: American Association of Geographers; American Geographic Society; Ameriško geografsko društvo; Ameriško združenje geografov; history of geography; Nacionalna geografska zveza; The National Geographic Society; USA; ZDA; zgodovina geografije